ρ PUPPIS: THE POSSIBILITY OF NON-RADIAL PULSATIONS - Yushchenko, A. V.; Dorokhova, T. N.; Gopka, V. F.; Kim, C. (Одеські астрономічні публікації, 2008)
The profiles of spectral lines in the high resolution (R=80,000) and high signal to noise ratio (S/N more than 300) VLT spectrum of ρ Pup are not symmetric. Under the assumption that the asymmetry of the observed profiles is introduced by nonradial pulsations we estimated the pulsational degree l=3, the azimuthal order m=1, and amplitude of pulsation 15 km s-1. The projected rotational velocity of the star is near v sin i =3.5 km s-1. The obtained synthetic spectrum yield the better fit to the observed one in comparison with earlier known parameters.